Mengetahui Tingkat Kekuatan Karakter Klee pada Game Genshin Impact Menggunakan Metode Klasifikasi dengan Algoritma Naïve Bayes - Putra Pratama, M. Faskal (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Video games are a form of interactive entertainment played via electronic devices such as computers, game consoles, smartphones, or tablets. Video games usually involve players in a virtual experience where they control characters or objects in the world created in the game. For example, genshin impact is played by many people because it has characteristics and uniqueness in the game, such as the combination of elements in each character, an interesting storyline, and much more. This study aims to assess a character based on the attributes possessed by the character whether it is strong or weak by using the naïve Bayes method. Through the classification carried out, the object to be chosen is a character named Klee to assess whether the character is strong or weak.